2013
DOI: 10.1097/scs.0b013e31829ad227
|View full text |Cite
|
Sign up to set email alerts
|

Complete Resection and Immediate Reconstruction With Costochondral Graft for Recurrent Aneurysmal Bone Cyst of the Mandibular Condyle

Abstract: Aneurysmal bone cyst is a non-neoplastic expansile lesion characterized by replacement with fibro-osseous tissue and blood-filled cavernous spaces. Involvement of the condyle is rare, and only 11 cases have been reported in English-language literature to date. Its common treatment modalities are lesion excision or condylar resection, but recurrence is high in patients treated with the former. The authors reported a 19-year-old female patient with swelling of the right preauricular region, who had a surgical cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Comparing the results of 8 cases of reconstruction in ABC condyle including this case [ Table 1 ][ 5 7 8 9 ] we found that, 62.5% cases has gone for costochondral graft either as a primary or in recurrence cases as an reconstructive option, while 25% cases has taken condylar prosthesis as an reconstructive option. Ettl et al .…”
Section: Discussionmentioning
confidence: 93%
“…Comparing the results of 8 cases of reconstruction in ABC condyle including this case [ Table 1 ][ 5 7 8 9 ] we found that, 62.5% cases has gone for costochondral graft either as a primary or in recurrence cases as an reconstructive option, while 25% cases has taken condylar prosthesis as an reconstructive option. Ettl et al .…”
Section: Discussionmentioning
confidence: 93%
“…The etiopathogenesis of aneurysmal bone cysts is highly debated, and according to the majority of reports, trauma history is the primary causative factor, followed by vascular abnormalities (3) and other factors. The same causative factors (4,5) are not present. ABC in the jaws can present radiographic variations, making it difficult to interpret the initial image exams that will guide the planning and subsequent treatment because there is a lack of specificity in the clinical and radiographic appearance (1,5).…”
Section: Introductionmentioning
confidence: 97%
“…The same causative factors (4,5) are not present. ABC in the jaws can present radiographic variations, making it difficult to interpret the initial image exams that will guide the planning and subsequent treatment because there is a lack of specificity in the clinical and radiographic appearance (1,5).…”
Section: Introductionmentioning
confidence: 97%
“…É descoberto, geralmente, por meio de radiografias de rotina e pode exibir lesões bem circunscritas uni ou multiloculares. [1][2][3][4][5][6][7][8][9] Histopatologicamente, o COA pode ser classificado como primário ou secundário, dependendo da ausência ou presença de outras lesões preexistentes, respectivamente. O COA secundário pode estar associado com fibroma ossificante central, fibroma cementoossificante, lesão central de células gigantes, lesões fibro-ósseas e osteoblastoma.…”
Section: Introductionunclassified